Critical Illness in HIV-Infected Patients in the Era of Combination Antiretroviral Therapy - Akgün, Kathleen M. (American Thoracic Society, 2011)
As HIV-infected persons on combination antiretroviral therapy (ART) are living longer and rates of opportunistic infections have declined, serious non–AIDS-related diseases account for an increasing proportion of deaths. Consistent with these changes, non–AIDS-related illnesses account for the majority of ICU admissions in more recent studies, in contrast to earlier eras of the AIDS epidemic. Although mortality after ICU admission has improved significantly since the earliest HIV era, it remains substantial. In this article, we discuss the current state of knowledge regarding the impact of ART on incidence, etiology, and outcomes of critical illness among HIV-infected patients. In addition, we consider issues related to administration of ART in the ICU and identify important areas of future research.